Low-moderate alcohol use effects on glycemic control of patients presenting in the ED - Dominick DeMasi; Laura Harrison; Fredrick A. Davis; Adam Berman; Sandeep Kapoor; Nancy Kwon (International Journal of Emergency Medicine)
Abstract Background The prevalence of Type 2 Diabetes Mellitus (DM2) is rising, affecting 462 million globally, including 21 million in the U.S. Emergency Department (ED) visits by adults with diabetes in the U.S. increased by 54% from 2012 to 2021 and represent a significant portion of global ED visits. Concurrently, 62% of U.S. adults report lifetime alcohol consumption. This study aimed to correlate AUDIT-C scores to changes in glucose and HbA1c levels in patients with DM2. Previous research has produced mixed results on whether light-to-moderate alcohol use improves or worsens glycemic control. Using a large urban ED dataset, this study seeks to better define this relationship and guide interventions for alcohol use in patients with DM2. Methods Data from Long Island Jewish ED (January 2022–October 2023) was analyzed. Patients were included based on an HbA1c ≥ 6.5 or a secondary discharge diagnosis of DM2. AUDIT-C scores were treated as a categorical variable, as no dose-dependent relationship was observed. Statistical analysis was conducted using SPSS 26. Results Non-zero AUDIT-C scores were significantly associated with increases in POCT-Blood Glucose, estimated average glucose, and HbA1c. A linear regression model showed an R-value of 0.047 (p < 0.001) for POCT-Blood Glucose in patients with HbA1c ≥ 6.5. Patients with an AUDIT-C score ≥ 1 had higher mean POCT-Blood Glucose (249.72 vs. 226.48, t = 4.240, p < 0.001). Estimated average glucose showed an R-value of 0.045 (p < 0.001), with a mean difference of 11.872 (t = 4.155, p < 0.001). For HbA1c, the R-value was 0.036 (p = 0.004), with higher levels in patients with AUDIT-C ≥ 1 (8.265 vs. 7.904, t = 2.844, p = 0.005). The effects were more pronounced in African-American and Asian-American populations. Conclusion Alcohol use, even at moderate levels (AUDIT-C = 1), was associated with higher glucose and HbA1c levels in patients with DM2, particularly among African-American and Asian-American populations. These findings suggest the need for substance use interventions at lower AUDIT-C thresholds and further considerations to mitigate future risk in this population.